2017
DOI: 10.18632/oncotarget.22502
|View full text |Cite
|
Sign up to set email alerts
|

Cymbopogon citratus and Camellia sinensis extracts selectively induce apoptosis in cancer cells and reduce growth of lymphoma xenografts in vivo

Abstract: Cancer cells are reported to have elevated levels of reactive oxygen species (ROS) and are highly dependent on cellular defense mechanisms against oxidative stress. Numerous nutraceuticals and natural polyphenolic compounds have a wide range of abilities to alter cellular redox states with potential implications in various diseases. Furthermore, therapeutic options for cancers are mostly nonselective treatments including genotoxic or tubulin-targeting compounds. Some of the natural extracts, containing multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 31 publications
(40 reference statements)
0
36
0
Order By: Relevance
“…Several reports have indicated that isolated polyphenolic components from plant materials have antitumor and anti-genotoxic properties (Philion et al, 2017;Surh & Ferguson, 2003). They showed that the polyphenolic components scavenge free radicals from the cells and consequently protect the cellular systems from oxidative damage inducing DNA fragmentation and tumor induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have indicated that isolated polyphenolic components from plant materials have antitumor and anti-genotoxic properties (Philion et al, 2017;Surh & Ferguson, 2003). They showed that the polyphenolic components scavenge free radicals from the cells and consequently protect the cellular systems from oxidative damage inducing DNA fragmentation and tumor induction.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the polyphenolic components scavenge free radicals from the cells and consequently protect the cellular systems from oxidative damage inducing DNA fragmentation and tumor induction. Additionally, extracted natural products are containing numerous bioactive components which probably are targeting many of pathways associated with cancer to induce apoptosis and consequently death of the tumor cells (Philion et al, 2017). It has been found that Nitraria retusa extracts have been recorded for anti-mutagenic and anti-oxidant activities as well as enhancing apoptosis which attributed to its contents of polyphenolic components (Boubaker et al, 2012a;Skandrani, Pinon, Simon, Ghedira, & Chekir-Ghedira, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports on the cytotoxicity of lemongrass essential oils have been conducted; however, the mechanism of action has been investigated in only a few studies [8,18]. An ethanol extract of lemongrass exhibited significant anticancer properties in lymphoma and leukemia models and effectively induced apoptosis in a recent study [19]. A proapoptosis effect of the polysaccharide fraction of C. citratus has also been demonstrated [20].…”
Section: Investigation On the Mechanism Of Action Of Lemongrassmentioning
confidence: 99%
“…Hibiscus flower ( Hibiscus rosa-sinensis ) were obtained from Premier Herbal Inc. (Toronto, ON, Canada). This aqueous extraction protocol is similar to that previously published with the following modifications [18, 19]. The flowers were grinded using a coffee grinder into a fine powder.…”
Section: Methodsmentioning
confidence: 99%